2012
DOI: 10.1007/s00262-012-1237-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of 4-1BB by monoclonal antibody PF-05082566 enhances T-cell function and promotes anti-tumor activity

Abstract: 4-1BB (CD137, TNFRSF9) is a costimulatory receptor expressed on several subsets of activated immune cells. Numerous studies of mouse and human T cells indicate that 4-1BB promotes cellular proliferation, survival, and cytokine production. 4-1BB agonist mAbs have demonstrated efficacy in prophylactic and therapeutic settings in both monotherapy and combination therapy tumor models and have established durable anti-tumor protective T-cell memory responses. PF-05082566 is a fully human IgG2 that binds to the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 48 publications
4
108
1
1
Order By: Relevance
“…Utomilumab (PF-05082566) is a novel, fully human IgG2 agonist mAb that binds with high affinity to 4-1BB/CD137, a costimulatory molecule induced upon T-cell receptor activation that promotes cell survival and enhances cytotoxic T-cell responses (8). Engagement of 4-1BB/CD137 by utomilumab induces T-cell proliferation, cytokine production, and inhibition of tumor growth in human peripheral blood lymphocyte severely compromised immunodeficient (SCID) xenograft models (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utomilumab (PF-05082566) is a novel, fully human IgG2 agonist mAb that binds with high affinity to 4-1BB/CD137, a costimulatory molecule induced upon T-cell receptor activation that promotes cell survival and enhances cytotoxic T-cell responses (8). Engagement of 4-1BB/CD137 by utomilumab induces T-cell proliferation, cytokine production, and inhibition of tumor growth in human peripheral blood lymphocyte severely compromised immunodeficient (SCID) xenograft models (8).…”
Section: Introductionmentioning
confidence: 99%
“…Engagement of 4-1BB/CD137 by utomilumab induces T-cell proliferation, cytokine production, and inhibition of tumor growth in human peripheral blood lymphocyte severely compromised immunodeficient (SCID) xenograft models (8). Preliminary results from a phase I study (NCT01307267) of single-agent utomilumab in patients with advanced solid malignancies and in combination with the anti-CD20 mAb rituximab in patients with relapsed or refractory CD20 þ non-Hodgkin lymphoma showed that treatment was well tolerated (up to an utomilumab dose of 10 mg/kg), with no dose-limiting toxicities (DLT), and provided preliminary evidence of clinical activity in these patient populations (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The TNF-family receptor, 4-1BB, is expressed on activated T cells and antibodies binding this receptor increase NF-κB activity resulting in cytokine production, leukocyte proliferation and antitumor efficacy in preclinical models [111]. MCPyV-specific T cells express elevated 4-1BB on their surface relative to other virusspecific cells suggesting that these cells may be particularly responsive to 4-1BB agonism [49].…”
Section: Anti-4-1bb (Cd137)mentioning
confidence: 99%
“…Costimulation by 4-1BBL/4-1BB interaction is fundamentally involved in the proliferation, differentiation, and survival of CD8 þ T cells, therefore thought to play an important role in potentiating cytotoxic T-cell immune responses (20). Antitumor effects were reported in several mouse models with agonistic 4-1BB-specific antibodies (21,22). Also, vaccination with tumor cells transfected to express a 4-1BB-specific antibody fragment (scFv) on the cell surface or admixture of them to wild-type tumor cells induced strong antitumor responses (23,24).…”
Section: Introductionmentioning
confidence: 99%